2013
DOI: 10.2478/10004-1254-64-2013-2351
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Indices Correlate with Dyslipidemia and Pro-Inflammatory Cytokine Levels in Fluoride-Exposed Rats

Abstract: The aim of this study was to establish the effects of fl uoride on lipid metabolism and attendant infl ammatory response by exposing rats to 50 mg L -1 and 100 mg L -1 of fl uoride through drinking water for seven weeks. Both concentrations led to hypercholesterolemia while the 100 mg L -1 concentration induced hypertriglyceridaemia. High density lipoprotein (HDL) cholesterol levels dropped in the exposed rats while interleukin 2 (IL-2) increased more than 1.5-fold (p<0.05) and IL-6 and plasma TNF-α more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
(34 reference statements)
3
9
0
Order By: Relevance
“…Herein, SF induced a significant rise in hepatic NF-κB, COX-2, and STAT-3, while Nrf2expression was decreased; this is in agreement with the findings of Afolabi et al, 47 Gutowska et al, 48 Jain et al, 49 and Mukhopadhyay et al, 50 who declared that fluoride affected the previous parameters in the same manner.…”
Section: Discussionsupporting
confidence: 90%
“…Herein, SF induced a significant rise in hepatic NF-κB, COX-2, and STAT-3, while Nrf2expression was decreased; this is in agreement with the findings of Afolabi et al, 47 Gutowska et al, 48 Jain et al, 49 and Mukhopadhyay et al, 50 who declared that fluoride affected the previous parameters in the same manner.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, in regard to IL-6, the seminar research of Liu et al found that F exposure mediated the expression of over 1000 genes in humans and was found to upregulate specifically the expression of interleukin 6 (IL6) in leucocytes [253]. These findings are in agreement with previous in vitro and in-vivo animal studies which also found that F can induce IL-6 mRNA expression and protein levels [254,255,256,257,258].…”
Section: Molecular Mechanisms Underlying Fluoride Contribution To supporting
confidence: 81%
“…The precise mechanism by which N sativa may induce its favorable potential on lipids and blood pressure is not fully elucidated. However, several lines of evidence are accumulating denoting a pivotal role for oxidative stress in the pathogenesis of dyslipidemia 37 and hypertension. 38 The beneficial effects of N sativa on lipid levels and blood pressure demonstrated in the current study may be explained by the high antioxidant potential of N sativa , reported previously.…”
Section: Discussionmentioning
confidence: 99%